How the media matters for the economic vote: Evidence from Britain - Chitralekha Basu (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
This study uses data from the 2005-10 British Election Panel Study to examine the effect of media coverage on voter evaluations of the incumbent government following the 2007-8 financial crisis. By combining sentiment analysis of newspaper content with an instrumental variables approach, I show that newspapers' coverage of these events influenced how their readers, and especially Labour-supporting readers, evaluated the Labour government's handling of the crisis and also the economy in general. I also show that newspaper framing of these events influenced readers' propensity to support Labour throughout the subsequent general election campaign. Formal sensitivity analyses provide further evidence that these effects are not driven by readers' previous assessments of the Labour party. I thus demonstrate that media framing of economic events, through its effects on reader evaluations of incumbents' economic competence, can have durable electoral implications.
Keywords: D72; D83; L82; 330; Political communication; Media effects; Economic voting